Acessibilidade: aplicação da ABNT NBR 9050:2004 no centro municipal de reabilitação Mário Dias Tavares em Santana/AP - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2014)
Disability is the loss or abnormality of a psychological, physiological or anatomical structure or function. According to Censo 2010, approximately 24% of brazilian population has some type of disability, and many of them, can’t live in dignified conditions because of architectural barriers present in the urban environment. From the review of norms relating to the subject, highlighting the ABNT NBR 9050:2004 which establishes guidelines to be followed in the planning of buildings, manufacturing equipment and securities organization in regard to accessibility, it appears many public buildings there’s no proper application of this rule, restricting the access of people with disabilities in various public buildings. In this research, were identified architectural barriers existing in the building of Municipal Rehabilitation Center Mário Dias Tavares, frequented daily by dozens of people with disabilities. The development of this research came about through a case study with bibliographic survey dated from 2000 to 2013; collection and analysis of data about the rehabilitation center through measures, photographic records and the use of the checklist, based on the determinations of ABNT NBR 9050:2004. From the data obtained, a site diagnosis and a viable proposal for the building retrofitting by means of a specific architectural design composed of three types of signaling was drawn up in order to exclude possible differences in access between users with disabilities or reduced mobility. This project aims to ensure the right to come and go of the person with physical, visual and hearing disability, so they will have full access to public agencies, in particular the CREMSA, contributing to the social recovery of the disabled population from Santana city.
Acessibilidade: aplicação da abnt nbr 9050:2004 no centro municipal de reabilitação Mário Dias Tavares em Santana/AP
Keywords: Arquitetura e deficientes - Legislação; Deficientes - Orientação e mobilidade; Edifícios públicos com acesso livre aos deficientes; Construção civil - Normas; Administração pública; CNPQ::CIENCIAS SOCIAIS APLICADAS